Marine clay soil stabilization with chemical by electrokinetic method - Ch'ng, Wei En (2018)
Marine clay is one of the problematic soil for all geotechnical engineers. Therefore, one of the soil stabilization methods, ElectroChemical Treatment (ECT) was introduced. ECT method was carried out by injecting the chemical (Calcium Hydroxide, Phosphoric Acid, and Calcium Chloride) into the cathode or anode through the electrokinetic technique. The chemical ions undergone chemical reaction with the exiting ion of the marine clay soil such as Alumino and Silicate to form Calcium Silicate Hydrate or AluminoPhosphate gel. Calcium Silicate Hydrate and AluminoPhosphte gel behaved as cementitious properties in the marine clay soil. Thus, the marine clay soil was finally stabilized. In this project, three treatments of soil stabilization by chemicals were identified such as Distilled Water – Distilled Water, Calcium Hydroxide – Phosphoric Acid and Calcium Chloride only injection into cathode and anode respectively. A control soil was prepared and identified in order to prove that the improvement of the marine clay soil was not the factor of moisture content but the reaction of the chemicals. Direct shear test (Shear Box) and unconfined compressive strength test (UCS) were carried out to determine the improvement of before treatment and after treatment marine clay soils. It was clearly found that, the second treatment (Calcium Hydroxide and Phosphoric Acid)
was the most effective treatment compared with others by improving about 60.5% in shear stress and 212.5% in compressive strength. Besides, the marine clay soil was improved without any injection of chemical (Treatment 1) but undergone eletrokinetic technique only. It can be proven through the Scanning Electron Microscopic (SEM) analysis.
Project paper (B.E. (Engineering Civil) – Universiti Putra Malaysia, 2018